Atypical Forms of Hand, Foot, and Mouth Disease: A Prospective Study of 47 Italian Children. Issue 4 (13th June 2016) - Neri, Iria; Dondi, Arianna; Wollenberg, Andreas; Ricci, Lorenza; Ricci, Giampaolo; Piccirilli, Giulia; Lazzarotto, Tiziana; Patrizi, Annalisa
Abstract: Background: Atypical forms of hand, foot, and mouth disease (HFMD) caused by coxsackievirus A6 have been reported in recent years. High fever and severe cutaneous lesions are common, whereas neurologic complications are rare. Eczematous areas of patients with atopic dermatitis show more lesions. The goal of the current study was to describe the clinical characteristics of children with atypical HFMD and to investigate the involvement of the different enterovirus serotypes associated. Methods: All patients referred to our service for atypical HFMD from January 2012 to February 2014 were enrolled and classified as having the diffuse form (lesions extended to the trunk), the acral form (lesions with a mainly acral distribution), or eczema coxsackium (lesions on preexisting eczematous areas). Results: Data from 47 patients were analyzed (median age 22 months [range 4–84 mos]); viral genotyping was performed in 11 cases. Sixty‐two percent of the subjects developed the acral form, 23% eczema coxsackium, and 15% the diffuse form. Most patients had a nonclassical vesicular eruption and moderate to severe extent of cutaneous involvement. Approximately 80% of patients had palmoplantar purpuric macules. Most children younger than 2 years old had the acral form, most patients with eczema coxsackium were age 2 years and older, and the diffuse form was similarly distributed between the two age groups. Coxsackievirus A6 was detected in 9 of 11 genotyped cases. Conclusion: Our prospective study allowed the identification of three HFMD phenotypes differing from the classical form. Clinical care of these patients should include symptomatic treatment of extracutaneous features and, if necessary, hospitalization for complications.